THE EFFECT OF CONDUCTING GOBAK SODOR TRADITIONAL GAMES ON STUDENTS’ BEHAVIOR IN SDN 10 MATARAM - Ulia Arta Sari; Nasruddin Nasruddin; Abdul Kadir Jaelani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2021)
Lack of independence of students solving problems with friends while playing or when the learning process is taking place. The problems that occur often make the parents intervene. Related to this problem, there is a game method that can train student cooperation and responsibility, the game is usually called Gobak Sodor. This game has a positive impact on students' attitudes and behavior. Thus, the writer wanted to know whether there was a significant effect of giving the traditional Gobak Sodor game on student behavior. The research technique used is to use quantitative methods. The research instrument used was a questionnaire. The data analysis technique used paired sample t-test, based on the results of the pretest and posttest, the average value of student behavior was 42.97 and the post-test was 46.94. The results of hypothesis testing obtained the value of Sig. (2-tailed) <0.05 at the pretest and posttest with a value of 0.000 <0.05. In accordance with hypothesis testing, namely the value of Sig. (2-tailed) <0.05, then Ho is accepted and Ha is rejected. This shows that there is an effect of giving the traditional Gobak Sodor game on student behavior.